Pengaruh Pemberian Kombinasi Limbah Decanter Solid dan Abu Boiler Kelapa Sawit terhadap Perubahan Beberapa Sifat Kimia Tanah Ultisols: The Effect of Combining Palm Oil Decanter Cake and Palm Oil Boiler Ash on Changes in Several Chemical Properties of Ultisols Soil - Riska Fitrianty Nurjanah; Muhammad Mahbub; Hairil Ifansyah (Acta Solum, 2025)
Ultisols is an acid mineral soil that has various problems namely high soil acidity, Al3+ concentration and nutrient poor. One way to increase soil fertility and quality is by using ameliorant. Palm oil waste can be used to make ameliorant. Palm oil decanter cake and palm oil boiler ash are the types of palm oil waste used in this research. Providing Palm oil decanter cake and palm oil boiler ash can increase pH, available N-mineral, P concentration, and K-dd in Ultisols. The aim of this research is to determine the effect of providing waste decanter solid and palm oil boiler ash on changes in several chemical properties of Ultisols soil and the best combination of palm oil solid waste (decanter solid) and palm oil boiler ash to improve several soil chemical properties, namely, pH, availability of nitrogen, phosphorus and potassium in Ultisols soil. This research used a Completely Randomized Design Method factorial with two factors, the first factor being a Palm oil decanter cake (0, 5, and 10 t ha-1) and the second factor is palm oil boiler ash (0, 5, and 10 t ha-1), with three repetitions. This research was carried out in a greenhouse and analyzed in a soil physics, chemistry and biology laboratory. The research results show a combination of Palm oil decanter cake and palm oil boiler ash have a significant effect on pH, N-mineral concentration, and available P and palm oil boiler ash itself can increase the concentration of K-dd.